Inflammation-mediated Notch signaling skews Fanconi Anemia hematopoietic stem cell differentiation - Du, Wei (2013)
Hematopoietic stem cells (HSCs) can either self-renew or differentiate into various types of cells of the blood lineage. Signaling pathways that regulate this choice of self-renewal versus differentiation are currently under extensive investigation. Here we report that deregulation of Notch signaling skews HSC differentiation in mouse models of Fanconi anemia (FA), a genetic disorder associated with bone marrow failure and progression to leukemia and other cancers. In mice expressing a transgenic Notch reporter, deletion of the Fanca or Fancc gene enhances Notch signaling in multipotential progenitors (MPPs), which is correlated with decreased phenotypic long-term HSCs and increased formation of MPP1 progenitors. Furthermore, we found an inverse correlation between Notch signaling and self-renewal capacity in FA hematopoietic stem and progenitor cells. Significantly, FA deficiency in MPPs deregulates a complex network of genes in the Notch and canonical NF-κB pathways. Genetic ablation or pharmacologic inhibition of NF-κB reduces Notch signaling in FA MPPs to near wide-type level, and blocking either NF-κB or Notch signaling partially restores FA HSC quiescence and self-renewal capacity. Taken together, these results suggest a functional crosstalk between Notch signaling and NF-κB pathway in regulation of HSC differentiation.